Contemporary Molecular Barium Chemistry. Issue 35 (30th July 2020) - Chapple, Peter M.; Sarazin, Yann
Abstract : Driven by the many potential applications as molecular catalyst for a range of metal‐promoted transformations, the quest for well‐defined, soluble and reactive complexes of barium has attracted substantial interest in the past decade. While it has long been overlooked, barium is now one of the hotly debated metals in main group chemistry. The present review surveys the main achievements of the last 10 years in the molecular chemistry of barium, presenting along the way the key synthetic strategies that have been implemented successfully to address the specificities of barium chemistry. This includes ligand design and non‐covalent interactions. The performances of barium complexes as homogeneous catalysts for the most prominent reactions mediated by alkaline‐earth metals (hydroelementations and heterodehydrocouplings) are reviewed in conjunction with those obtained with somewhat more common calcium or strontium catalysts. Abstract : An up‐to‐date survey of the recent progress in the molecular chemistry of barium is presented. It covers the synthesis of well‐defined, soluble barium complexes and their performance as homogeneous catalysts in a variety of reactions such as hydroelementations and dehydrocouplings.